2022
DOI: 10.1177/18479790221141537
|View full text |Cite
|
Sign up to set email alerts
|

The impact of big data analytics on organizational sustainability: The influencing factors of autonomous research and development and absorptive capacity

Abstract: This study aims to see how the big data analytics capability (BDAC) and its dimensions affect the absorptive capacity and autonomous R&D of high-speed railways. As well as their impact on the organization’s long-term sustainability, using the mediation of absorptive capacity and autonomy in R&D. Employees and the heads of the planning, HR, R&D, and technical departments of high-speed railways were polled for information. For data analysis, we used PLS-SEM, and then we employed mediation analysis. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…It makes firms optimize the technology to influence business sustainable performance. Advanced technological developments that transform business functions help firms achieve sustainable performance [ 45 ]. In today's era, digital exploration activities are the most efficient way of improving the firm's sustainable performance.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…It makes firms optimize the technology to influence business sustainable performance. Advanced technological developments that transform business functions help firms achieve sustainable performance [ 45 ]. In today's era, digital exploration activities are the most efficient way of improving the firm's sustainable performance.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The literature stated that absorptive capacity mediates the relationship between BDA capabilities and strategic business value (Persaud and Zare, 2023). Arshad et al (2022) found that BDA capabilities positively impact absorptive capacity and mediate the relationship between BDA and organizational sustainable development. Understanding whether BDA capabilities enhance entrepreneurs' eco-business agenda and goals is crucial, especially in the existence of GAC.…”
Section: Green Absorptive Capacity Knowledge Sharing and Geomentioning
confidence: 99%